Carbo-cyclohexadienes vs. carbo-benzenes: structure and conjugative properties12. Issue 2 (21st November 2014) - Rives, Arnaud; Baglai, Iaroslav; Barthes, Cécile; Maraval, Valérie; Saffon-Merceron, Nathalie; Saquet, Alix; Voitenko, Zoia; Volovenko, Yulian; Chauvin, Remi
Abstract : Stable dichromic carbo -cyclohexadiene chromophores are synthesised, selectively with respect to the corresponding carbo -benzenes, by fluorine "chemical locking". Abstract : Ideally C s -/ C 2v -symmetric chromophores, constituted by two electro-active groups conjugated through the carbo -mer of the cyclohexa-1, 3-diene core, are selectively prepared by the SnCl2 -mediated reduction of tailored hexaoxy-[6]pericyclynes: in the latter substrates, one of the 1, 4-dioxybut-2-yne edges is "chemically locked" by two CF3 substituents preventing complete reduction to the corresponding aromatic carbo -benzenic core, which is expected to be more "π-insulating" between the electro-active ends. The bis-trifluoromethylated carbo -cyclohexadiene products are also shown to be significantly stabilized with respect to their bis-phenylated analogues. Their structural (crystal X-ray diffraction analyses), spectroscopical (NMR and UV-vis spectra), physio-optical (dichromism in solution) and electrochemical (cyclic voltammograms) properties are compared on the basis of the electron-donating/electron-withdrawing nature of the substituents. These properties are also compared with those of their aromatic carbo -benzene and flexible carbo-n -butadiene counterparts.